ADHD and growth: questions still unanswered - Ptacek, Radek; Kuzelova, Hana; Stefano, George B; Raboch, Jirí; Kream, Richard M; Goetz, Michal (Neuro endocrinology letters, 2014)
Attention deficit hyperactivity disorder (ADHD) is one of the most commonly diagnosed childhood psychiatric disorders. It is manifested in every part of an affected child's behavior, with multiple symptomatology and heterogenous etiology. Published studies report that ADHD children may show changes in growth and development. Most of the studies on ADHD have been focused on connections between medication and growth changes and describe growth delays associated with medication. However, recent research results point to the low significance of the changes accompanying pharmacological treatment. Changes in growth may not only be a secondary effect of the treatment, but may also be specific characteristics of ADHD.
Keywords: Child; Attention Deficit Disorder with Hyperactivity; Central Nervous System Stimulants; hyperkinetická porucha; růst; dítě; Growth; Child Development; stimulanty centrálního nervového systému; lidé; vývoj dítěte; Humans